2002
DOI: 10.1002/ajmg.10241
|View full text |Cite
|
Sign up to set email alerts
|

Five additional Costello syndrome patients with rhabdomyosarcoma: Proposal for a tumor screening protocol

Abstract: We report five new cases of rhabdomyosarcoma (RMS) in Costello syndrome. These cases, combined with those previously reported, increase the number of solid tumors to 17 (10 RMSs, 3 neuroblastomas, 2 bladder carcinomas, 1 vestibular schwannoma, 1 epithelioma), in at least 100 known Costello syndrome patients. Despite possible ascertainment bias, and the incomplete identification of all Costello syndrome patients, the tumor frequency could be as high as 17%. This is comparable to the 7–21% frequency of solid tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
144
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(152 citation statements)
references
References 27 publications
6
144
0
2
Order By: Relevance
“…The patients we report have had 3, 3.5, and 7 years of GH treatment with no evidence of neoplasia. They currently undergo regular tumor surveillance screening as recommended by Gripp et al [2002]. Monitoring of GH treatment to maintain insulin like growth factor-1 (IGF-1), a marker of GH action, within physiologic range has been suggested as a tool to minimize risk of neoplasia in this population [Pollak, 2000].…”
Section: Discussionmentioning
confidence: 99%
“…The patients we report have had 3, 3.5, and 7 years of GH treatment with no evidence of neoplasia. They currently undergo regular tumor surveillance screening as recommended by Gripp et al [2002]. Monitoring of GH treatment to maintain insulin like growth factor-1 (IGF-1), a marker of GH action, within physiologic range has been suggested as a tool to minimize risk of neoplasia in this population [Pollak, 2000].…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal and pelvic ultrasound and urine testing for catecholamine metabolites and hematuria were suggested. 48 However, a subsequent report 49 on elevated catecholamine metabolites in individuals with Costello syndrome without an identifiable tumor concluded that screening for abnormal catecholamine metabolites is not helpful. Serial abdominal and pelvic ultrasound screening for rhabdomyosarcoma and neuroblastoma was proposed every 3-6 months until age 8-10 years.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
“…Urinalysis for hematuria was suggested annually beginning at age 10 years to screen for bladder cancer. 48 Neither of these screening approaches has yet been proven to be beneficial; however, studies are ongoing. The most important factor for early tumor detection remains parental and physician awareness of the increased cancer risk.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%
“…Most patients also have cardiac defects, musculoskeletal anomalies, and neurocognitive impairment (13). Subjects with CS have multiple papillomas and an increased risk of developing rhabdomyosarcomas and bladder carcinomas (14)(15)(16)(17). About 80% of individuals affected with CS have HRAS mutations encoding mutant G proteins with comparatively weak transforming activity, primarily HRAS G12S .…”
mentioning
confidence: 99%